Ferrimagnetic Tb–Fe Alloy Thin Films: Composition and Thickness Dependence of Magnetic Properties and All-Optical Switching - Hebler, Birgit; Hassdenteufel, Alexander; Reinhardt, Patrick; Karl, Helmut; Albrecht, Manfred (Frontiers in Materials, 2016)
Ferrimagnetic rare earth – transition metal Tb–Fe alloy thin films exhibit a variety of different magnetic properties, which depend strongly on composition and temperature. In this study, first the influence of the film thickness (5–85 nm) on the sample magnetic properties was investigated in a wide composition range between 15 and 38 at.% of Tb. From our results, we find that the compensation point, remanent magnetization, and magnetic anisotropy of the Tb–Fe films depend not only on the composition but also on the thickness of the magnetic film up to a critical thickness of about 20–30 nm. Beyond this critical thickness, only slight changes in magnetic properties are observed. This behavior can be attributed to a growth-induced modification of the microstructure of the amorphous films, which affects the short range order. As a result, a more collinear alignment of the distributed magnetic moments of Tb along the out-of-plane direction with film thickness is obtained. This increasing contribution of the Tb sublattice magnetization to the total sample magnetization is equivalent to a sample becoming richer in Tb and can be referred to as an “effective” composition. Furthermore, the possibility of all-optical switching, where the magnetization orientation of Tb–Fe can be reversed solely by circularly polarized laser pulses, was analyzed for a broad range of compositions and film thicknesses and correlated to the underlying magnetic properties.